480 Catheter pulmonary vein ablation vs. medical therapy or atrioventricular node ablation and resynchronization in patients with atrial fibrillation and heart failure: a systematic review and meta-analysis. (8th December 2021) - Liccardo, Gaetano; Cannata, Francesco; Chiarito, Mauro; Bombace, Sara; Maccallini, Marta; Villaschi, Alessandro; Pinto, Giuseppe; Fazzari, Fabio; Pini, Daniela; Bragato, Renato Maria; Condorelli, Gianluigi; Cappato, Riccardo; et al.
Abstract: Aims: Atrial fibrillation (AF) and heart failure (HF) are increasing in prevalence worldwide and, when present altogether, are associated with significant mortality and morbidity. Several and recent randomized clinical trials have reported an improvement of clinical outcomes in patients with HF and AF with catheter ablation. To provide a comprehensive and updated synthesis of effect estimates of the available randomized and observational clinical trials comparing pulmonary vein isolation with optimal medical therapy (rate or rhythm) or atrioventricular node ablation and resynchronization. Methods and results: MEDLINE database was searched from inception to 4 March 2021 by two reviewers (F.C. and M.C.) for relevant studies. The following key words were used: 'atrial fibrillation', 'heart failure', 'ablation', 'medical', 'drug', 'rate', 'rhythm', 'resynchronization', and 'atrial flutter'. The co-primary outcomes were all-cause death and hospitalization for HF. A total of 16 studies enrolling 42 908 patients were included; of these, 9 were randomized controlled trials, 3 unadjusted observational studies, and 4 adjusted observational trials. Patients treated with catheter ablation had a statistically significant reduction for the risk of all-cause death {Figure on the left: odds ratio [OR]: 0.51, [95% confidence interval (CI): 0.31–0.84], P  = 0.008, NNT 33} and hospitalization for HF [Figure on the right: OR: 0.52, (95% CI: 0.31–0.87), P 0.014, NNT 24]. Subgroup analysis confirmed these results only in HF with reduced ejection fraction subgroup. Meta-regression analyses showed a direct correlation between a higher burden of persistent/long-standing persistent AF and the positive impact of catheter ablation of AF. Moreover, the age of 70 years emerged as the cut-off age for a greater impact of catheter ablation. Conclusions: Catheter ablation of AF is associated with a lower risk of all-cause death and HF hospitalizations in patients with AF and HF, as compared to medical therapy or atrioventricular node ablation and resynchronization. These results are mainly applicable for HF with reduced ejection fraction.